2016
DOI: 10.1038/srep21805
|View full text |Cite
|
Sign up to set email alerts
|

Can arbuscular mycorrhizal fungi reduce Cd uptake and alleviate Cd toxicity of Lonicera japonica grown in Cd-added soils?

Abstract: A greenhouse pot experiment was conducted to study the impact of arbuscular mycorrhizal fungi−Glomus versiforme (Gv) and Rhizophagus intraradices (Ri) on the growth, Cd uptake, antioxidant indices [glutathione reductase (GR), ascorbate peroxidase (APX), superoxide dismutase (SOD), catalase (CAT), ascorbate (ASA), glutathione (GSH) and malonaldehyde (MDA)] and phytochelatins (PCs) production of Lonicera japonica in Cd-amended soils. Gv and Ri significantly increased P acquisition, biomass of shoots and roots at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(49 citation statements)
references
References 56 publications
6
38
1
4
Order By: Relevance
“…No differences in Cd, P, or Fe contents were found between nM and M soybean soils. This result is in agreement with the Cd concentration values in soil reported for Lonicera japonica colonized by Glomus versiforme and R. intraradices [28]. Based on our results, we can only propose some possible explanations for this lack of differences in Cd, P, and Fe soil concentrations between M and nM soybean.…”
Section: Soil and Plant CD P And Fe Contentssupporting
confidence: 92%
“…No differences in Cd, P, or Fe contents were found between nM and M soybean soils. This result is in agreement with the Cd concentration values in soil reported for Lonicera japonica colonized by Glomus versiforme and R. intraradices [28]. Based on our results, we can only propose some possible explanations for this lack of differences in Cd, P, and Fe soil concentrations between M and nM soybean.…”
Section: Soil and Plant CD P And Fe Contentssupporting
confidence: 92%
“…Reported effects of AMF colonization on plant metal uptake are similarly inconsistent (e.g. Diaz et al 1996; Turnau and Mesjasz-Przybylowicz 2003; Chen et al 2005; Jiang et al 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Other studies, largely in greenhouses, have typically found that metals decrease AMF colonization and/or diversity (del Val et al 1999a, b, Khan 2001, Chen et al 2005, although Diaz et al (1996) and Tan et al (2015) found no effect of applied Zn, Pb, or Cd solutions on AMF colonization of three host plants, and Vogel-Miku s et al (2006) found that increasing soil Cd and Pb by mixing contaminated and uncontaminated soils in different ratios increased AMF colonization of the hyperaccumulator Thlaspi praecox. Reported effects of AMF colonization on plant metal uptake are similarly inconsistent (e.g., Diaz et al 1996, Turnau and Mesjasz-Przybylowicz 2003, Chen et al 2005, Jiang et al 2016.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plants can detect and respond to stresses in various ways that support their nourishment. [34][35][36] Plants not only recognize the previous exposure to stresses but also the mechanisms involved in defense, and again when the same stress exposes, they can adapted consequently. [37] The most obvious effect of unfavourable conditions initially appear at the cellular levels after that, physiological symptoms are observable.…”
Section: Diminishing Of Physiological Process Of Plantmentioning
confidence: 99%